Effect of short time precise dietary energy–protein in reproductive parameters of local crossbred dairy goats - Sitaresmi, Pradita Iustitia; Hudaya, Mohammad Firdaus; Kumala, Seraphina; Herdis, Herdis; Sofyan, Ahmad; Bintara, Sigit; Widyobroto, Budi Prasetyo; Widayat, Diah Tri (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to establish and focus on the implications of precise energy and protein levels on reproductive performance. This study based on field facts showed that excessive feed intake, especially protein intake, to increase productivity will lead to some decreased reproductive efficiency through disruption of reproductive hormonal compound biosynthesis or increasing blood urea nitrogen (BUN), which has rarely been studied. Materials and Methods: Healthy and mature Saanen crossbred goats raised by traditional farmers (2–4 years old; ± 45 kg) were divided into three experimental groups [T0 = basal feed according to the feed provided by farmers, T1 = protein and energy balanced feed according to National Research Council (NRC) (±5%), T2 = feed >20% excess protein, and excess energy from NRC] (n = 75). The factorial method was used in the experimental design with a post-hoc least significant difference test. Results: The data showed a significant difference (p < 0.05) in the biochemical or hormonal parameters between the control and the treatment groups. Also, T1 showed leads in any blood profile and reproductive hormone parameters such as total protein (79.6 ± 5.3 gm/dl), cholesterol (3.26 ± 0.47 mmol/l), progesterone (1.79 ± 2.21 ng/ml), and estrogen (47.85 ± 5.51 pg/ml), as well as the lowest levels of BUN (11.6 ± 1.59 mmol/l) and cortisol (25.07 ± 14.85 ng/ml) levels. T1 had the highest reproductive potential after treatment. Conclusion: The adverse effects of high and low protein consumption on reproductive hormones seem to be related to the blood profile and ovarian function, as hormone concentrations change significantly and lead to reproductive impairment. The data showed that balanced nutrient levels (5%/T1) resulted in excellent blood and hormone parameters. J. Adv. Vet. Anim. Res., 10(2): 257–268, June 2023 http://doi.org/10.5455/javar.2023.j677